Characterization of Two Trichinella spiralis Adult-Specific DNase II and Their Capacity to Induce Protective Immunity - Qi, Xin; Yue, Xin; Han, Yue; Jiang, Peng; Yang, Fan; Lei, Jun J.; Liu, Ruo D.; Zhang, Xi; Wang, Zhong Q.; Cui, Jing (Frontiers in Microbiology, 2018)
Deoxyribonuclease II (DNase II) is a widespread endonuclease which can degrade the DNA. Trichinella spiralis adult-specific DNase II-1 (TsDNase II-1)/DNase II-7 (TsDNase II-7) were identified in excretory–secretory (ES) or surface proteins of adult worm (AW) and intestinal infective larvae (IIL) using immunoproteomics with early infection sera. The aim of this study was to characterize the two T. spiralis DNase II and to investigate their potential for the vaccine candidate target molecules. The cDNA sequences of the two DNase II from 3 d AW of T. spiralis were cloned and expressed. The sequencing results showed that the complete cDNA sequences of the two DNase II were 1221 and 1161bp, the predicted open reading frame encoding 347 and 348 amino acids, respectively. On Western blot analysis, natural TsDNase II-1 and TsDNase II-7 in crude extract of IIL, AW and newborn larvae (NBL), and AW ES proteins were recognized by both anti-rTsDNase II-1 and anti-rTsDNase II-7 serum. qPCR and indirect immunofluorescent test (IIFT) showed the two DNase II were highly expressed at AW and NBL stages, and mainly located at the cuticle and stichosome of the nematode. Vaccination with two recombinant DNase II triggered prominent humoral responses that exhibited significant immune protection against T. spiralis larval infection, as demonstrated by notable reduction in intestinal AW and muscle larva burdens. Specific antibodies to the two molecules evidently inhibited the in vitro parasite invasion of enterocytes and participated in the killing of NBL by an ADCC mode. DNase II-1/DNase II-7 are the potential target molecules for anti-Trichinella vaccine for both blocking larval invasion and development.